Navigating the valley of death: Open innovation strategies for start-up survival - Yulissa Navarro-Castillo; Katia Mastrostefano; Mercedes Grijalvo; Gustavo Morales-Alonso (Entrepreneurial Business and Economics Review (EBER), 2024)
Objective: The objective of the article is to showcase the utilisation of open innovation in new technology-based firms (NTBFs) from the perspective of entrepreneurs who have successfully survived the crossing of the valley of death. We examined the interplay of open innovation (OI), and the entrepreneurial background (i.e. human capital, entrepreneurial education) to identify success factors in crossing the valley of death. Research Design & Methods: The research was qualitative and based on interviews conducted with founders of ten start-ups based in Madrid, Spain. To process the information obtained in a more objective manner, we utilised three R codes for qualitative data analysis. Subsequently, we employed word clouds to condense the interviews and ascertain the most significant variables related to the success of the ventures and OI. Findings: There were several recurring components among the entrepreneurs that have enabled them to successfully cross the valley of death. During the early stages, the entrepreneurship background becomes apparent, enabling them to implement their ideas based on the experience and knowledge acquired. In the subsequent stage, the emergence of family support for entrepreneurship facilitates access to initial financing beyond one's own savings invested. Therefore, it appears that human capital and access to informal sources of finance are more critical for entrepreneurial success than open innovation. Implications & Recommendations: Despite the fact that open innovation facilitates the acquisition of new knowledge from a theoretical standpoint, our results suggest that prioritising entrepreneurs' human capital and ensuring access to financing are more crucial in overcoming the valley of death, by optimizing the efforts of various stakeholders. Contribution & Value Added: The article offers a comprehensive understanding of the survival process of non-traditional business enterprises (NTBFs) and categorises three distinct variables that contribute to comprehending the significance of external and internal factors to which entrepreneurs are exposed.
Keywords: O36; M13; L26; 330; open innovation; start-up; entrepreneur; social support; professional experience